Weather Extremes Led to Large Variability in O3 Pollution and Associated Premature Deaths in East of China - Wan, Yu; Yin, Zhicong; Huo, Qianyi; Zhou, Botao; Wang, Huijun (Frontiers in Earth Science, 2022)
As global warming intensifies, hot extremes and heavy precipitation frequently happen in East of China. Meanwhile, severe surface ozone (O3) pollution resulting from the interactions of anthropogenic emissions and meteorological conditions also occur more frequently. In this study, we quantified the impact of weather extremes on ground-level O3 concentration during the summers of 2015–2021 and associated premature deaths in East of China. The O3 pollution influenced by hot extremes [maximum 8-h average O3 concentration (MDA8 O3) = 152.7 μg m−3] was 64.2% more severe than that associated with heavy rain (MDA8 O3 = 93 μg m−3) on the daily time scale. The compound hot and dry air extremes had a larger impact, and the associated MDA8 O3 could be up to 165.5 μg m−3. Thus, weather extremes could drastically perturb the O3 level in the air to exhibit large variability. Based on GEOS-Chem simulations with fixed anthropogenic emissions, forcing of weather extremes could successfully reproduce the large daily variability of O3 concentration because the weather extremes significantly influenced the physicochemical processes in the atmosphere. Furthermore, hot extremes magnified the single-day O3-related premature death to 153% of that under other-condition events, while heavy rain events decreased it to 70% in East of China. The findings of the present study have the potential to promote daily to weekly O3 forecasts and further improve our comprehensive understanding of the health effects of weather extremes and air pollution.